2023
DOI: 10.1186/s42269-023-00982-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics profile map of clinical A. baumannii strains isolated from health institutions in Turkey: a database search study and analysis of publications from 2011 to 2022

Abstract: Background Acinetobacter baumannii is recognized as a major threat that causes healthcare-associated infections and causes a huge challenge to the health system worldwide. This research study was designed to detect the types and profiles of antibiotics tested against A. baumannii clinical strains in Turkey to evaluate their effectiveness and reevaluate their usage. Main body of the abstract The study depended on data search strategy using the onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The bacterium has intrinsic resistance to a broad range of antibiotics, and acquired resistance mechanisms, such as enzymes inactivating antibiotics, have emerged. The high resistance rate of A. baumannii to Ceftazidime (94.11%), (Cefepime 88.23%) imipenem (77.77%) (Abed et al, 2023) and high mortality rates (50%-64%) have made it a priority-I pathogen according to the World Health Organization, which placed critical category for the urgent need of new antibiotics (Kieny, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium has intrinsic resistance to a broad range of antibiotics, and acquired resistance mechanisms, such as enzymes inactivating antibiotics, have emerged. The high resistance rate of A. baumannii to Ceftazidime (94.11%), (Cefepime 88.23%) imipenem (77.77%) (Abed et al, 2023) and high mortality rates (50%-64%) have made it a priority-I pathogen according to the World Health Organization, which placed critical category for the urgent need of new antibiotics (Kieny, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The K. pneumoniae genome contains multiple clusters of genes for chaperones and adhesin proteins for the assembly of fimbriae ( fim, ecp, mrk, kpa , and kpg gene clusters) . Biofilm formation also contributes to the persistence of A. baumannii in the hospital environment, , increasing the risk of cross-contamination and reinfection. Adhesion proteins help A. baumannii and P. aeruginosa cells attach to surfaces and initiate biofilm formation, which includes fimbriae and type IV pili. Moreover, studies have shown the role of curli fimbriae genes ( csgA and csgD ) in the biofilm formation of Enterobacter isolates .…”
Section: Biofilms: Fundamental Perspectivementioning
confidence: 99%